Dapagliflozin Alleviates Renal Fibrosis by Inhibiting RIP1-RIP3-MLKL-Mediated Necroinflammation in Unilateral Ureteral Obstruction - Xuan, Mei Ying; Piao, Shang Guo; Ding, Jun; Nan, Qi Yan; Piao, Mei Hua; Jiang, Yu Ji; Zheng, Hai Lan; Jin, Ji Zhe; Li, Can (Frontiers in Pharmacology, 2022)
Dapagliflozin, a sodium-glucose cotransporter-2 inhibitor, offers renoprotection in diabetes. However, potential for use in nondiabetic kidney disease remains unknown. Herein, we assessed whether dapagliflozin alleviates renal fibrosis by interfering with necroinflammation in a rat model of unilateral ureteral obstruction (UUO) and in vitro. After induction of UUO, rats were administered dapagliflozin daily for 7 consecutive days. UUO induced significant renal tubular necrosis and overexpression of RIP1-RIP3-MLKL axis proteins; these coincided with NLRP3 inflammasome activation, and subsequent development of renal fibrosis. Oxidative stress caused by UUO is tightly associated with endoplasmic reticulum stress and mitochondrial dysfunction, leading to apoptotic cell death through Wnt3α/β-catenin/GSK-3β signaling; all of which were abolished by both dapagliflozin and specific RIP inhibitors (necrostatin-1 and GSK872). In H2O2-treated HK-2 cells, dapagliflozin and RIP inhibitors suppressed overexpression of RIP1-RIP3-MLKL proteins and pyroptosis-related cytokines, decreased intracellular reactive oxygen species production, and apoptotic cell death, whereas cell viability was improved. Moreover, activated Wnt3α/β-catenin/GSK-3β signaling was inhibited by dapagliflozin and Wnt/β-catenin inhibitor ICG-001. Our findings suggest that dapagliflozin ameliorates renal fibrosis by inhibiting RIP1-RIP3-MLKL-mediated necroinflammation via Wnt3α/β-catenin/GSK-3β signaling in UUO.